USE OF AGRICULTURAL POTENTIAL FOR ECONOMIC RECOVERY/GROWTH - Ana-Maria IFRIM; Marius-Mihai MICU; Oana-Raluca RUSU; Catalin Ionut SILVESTRU; Cristina Vasilica ICOCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the current context, after a pandemic that has left traces in all socio-economic fields and during major geo-political problems, Basic research is needed in order to identify directions for rapid and sustainable socio-economic recovery. The agricultural sector has played a particularly important role in speeding economic growth and development in less developed countries. As a result, we may argue that the agriculture sector has aided these countries' integration into global trade. The proposed paper aims to identify the degree of dependence of the Moldovan economy on agriculture and how this dependence can be transformed into a challenge that will help the country's economy. Also, the paper aims to identify the link between agricultural production and gross domestic product at the level of the Moldovan economy, as well as the need to create a stability in the labour market in agriculture. The above mentioned will be achieved in the conditions in which there is already a decrease in the labour force, a decrease due to medical, geo-political and migration factors. To develop a sustainable economy, sustainable agricultural public policies must be enacted, resulting in the attraction of personnel from metropolitan regions (where unemployment is higher) to rural areas.